2022
DOI: 10.20885/jielariba.vol8.iss2.art6
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Online Zakat during the Covid-19 Pandemic by Amil Zakat Institutions in Boyolali, Indonesia

Abstract: Zakat is the third pillar of Islam that should be fulfilled for Muslims and has a high worship value in Allah SWT. The existence of this zakat can alleviate poverty and increase state income if a country can optimize the collection of zakat funds. One way to optimize the collection is to use digital technology. At this time, the amil zakat institution has harnessed the complexity of digital technology to collect zakat funds online. This study aims to determine the effectiveness of online zakat and which amil z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Some studies have examined how Zakat institutions have responded to the pandemic. For example, a study conducted in Indonesia found that Zakat institutions increased their distribution of Zakat funds during the pandemic to help those affected by the crisis (Akram H et al, 2022;Hakim & Setyaningsih, 2022;Hasan & Kamiluddin, 2021;Hudaefi et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some studies have examined how Zakat institutions have responded to the pandemic. For example, a study conducted in Indonesia found that Zakat institutions increased their distribution of Zakat funds during the pandemic to help those affected by the crisis (Akram H et al, 2022;Hakim & Setyaningsih, 2022;Hasan & Kamiluddin, 2021;Hudaefi et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%